2005
DOI: 10.1111/j.1365-2842.2005.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical marginal and internal gaps of Procera AllCeram crowns

Abstract: This study evaluated the marginal and internal gaps of Procera AllCeram crowns in vivo using silicone materials. Ninety Procera AllCeram crowns were evaluated before final cementation. White and black silicone materials were used to record the marginal and internal fit; then the crowns were sectioned bucco-lingually and mesio-distally to measure the thickness of the silicone layer using a microscope. Sixteen reference points were measured on each specimen. Mean marginal gaps among anterior, premolar and molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
136
3
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(154 citation statements)
references
References 14 publications
4
136
3
11
Order By: Relevance
“…There is a consensus between a series of studies that a marginal opening below 120 µm is clinically acceptable. 3,27,28 In this study, a mean marginal gap of 47 µm was found, which is well below the clinical threshold. This is an important finding since the marginal adaptation is an important criterion for the success of all-ceramic restorations in the long term.…”
Section: Discussionmentioning
confidence: 87%
“…There is a consensus between a series of studies that a marginal opening below 120 µm is clinically acceptable. 3,27,28 In this study, a mean marginal gap of 47 µm was found, which is well below the clinical threshold. This is an important finding since the marginal adaptation is an important criterion for the success of all-ceramic restorations in the long term.…”
Section: Discussionmentioning
confidence: 87%
“…Mechanical strength was reported in several researches [12,[56][57][58]. Several researchers have reported marginal gaps both in vitro and in vivo [59][60][61]. The large gap may cause cement solubility and result in plaque accumulation, marginal leakage, second caries, and eventually crown failure [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…The vertical gap between the restoration prosthesis and the die has been measured in previous evaluations of the fit of crown prostheses. Therefore, we measured gaps between the crown prostheses and dies to permit comparison with other reports 1,10,[19][20][21][22][23] . Fitness tests were performed for three abutment teeth with different cervical margin designs.…”
Section: Discussionmentioning
confidence: 99%